Computational studies of Bridelia retusa phytochemicals for the identification of promising molecules with inhibitory potential against the spike protein and papain-like protease of SARS-CoV-2 (Sciences of Phytochemistry, 2022)
SARS-CoV-2 is the pathogen responsible for the on-going COVID-19 pandemic. The two proteins namely, spike protein and papain-like protease are mainly responsible for the penetration and transmission of the virus, respectively. The objective of our study was to find the most promising phytoconstituents of Bridelia retusa that can inhibit both the proteins. Molecular docking, protein-ligand interactions, and molecular dynamics (MD) simulation techniques were used in the study. Bepridil and the co-crystal inhibitors of each protein were used as the standards. All the 14 phytoconstituents along with the standard drug and the co-crystal inhibitor of each protein were subjected to molecular docking. Ten compounds showed better binding affinities than the standards against the spike protein and 7 compounds have shown better binding affinities than the standards against papain-like protease protein. From the protein-ligand interactions, a total of 3 out of 10 for the spike protein and 5 out of 7 for the papain-like protease showed better interactions than the standards. An all-atom MD simulations study revealed that (R)4-(1,5-dimethyl-3-oxo-4-hexenyl)-benzoic acid formed the most stable complex with both proteins. The in-silico study provides an evidence for (R)4-(1,5-dimethyl-3-oxo-4-hexenyl)-benzoic acid as a promising inhibitor of the spike and papain-like protease of SARS-CoV-2. Further investigations such as in-vitro/in-vivo studies are recommended to validate the potency of (R)4-(1,5-dimethyl-3-oxo-4-hexenyl)-benzoic acid.